Dinamika Pelembagaan Partai Islam di Pemilu 2024; Studi Kasus Partai Kebangkitan Bangsa, Partai Keadilan Sejahtera, dan Partai Persatuan Pembangunan - Muhaimin, Ramdhan; Fadlillah, Syafiuddin; Asri, Rahman (Jurnal Politikom Indonesiana, 2024)
The most surprising phenomenon in the 2024 General Election is the failure of the United Development Party (PPP) to the House of Representatives of the Republic of Indonesia (DPR RI) as it failed to break the parliamentary threshold. As the Islamic party, the PPP’s failure in this election is certainly a disaster for Indonesian Islamic politics. However, two other Islamic parties still survive and qualify for parliament: the National Awakening Party (PKB) and the Prosperous Justice Party (PKS). Both parties are not only able to survive but also get electoral bonuses. Why should the party founded in 1973, ultimately fail in the 2024 elections? This study analyzes the institutionalization factors in the PPP’s failure and the PKB and PKS's success in the 2024 Election. This study analyzes the institutionalism factor that led to the PPP’s failure in the 2024 elections. This study uses the theory of institutionalization to explore the answers to the research formulation. The relevancy of the theory lies in the problem of the PPP in articulating the party's functions and institutions well in the ever-changing contestation of Indonesian democracy. Meanwhile, PKB and PKS are considered to be able to optimize the functions of political parties which shows the maturity of both compared to PPP. Keywords: Democracy, General Election, Islamic Party, Institutionalism, Political Islam